Potassium channel-based optogenetic silencing. Issue 1 (December 2018) - Bernal Sierra, Yinth Andrea; Rost, Benjamin; Pofahl, Martin; Fernandes, António; Kopton, Ramona; Moser, Sylvain; Holtkamp, Dominik; Masala, Nicola; Beed, Prateep; Tukker, John; Oldani, Silvia; Bönigk, Wolfgang; et al.
Abstract Optogenetics enables manipulation of biological processes with light at high spatio-temporal resolution to control the behavior of cells, networks, or even whole animals. In contrast to the performance of excitatory rhodopsins, the effectiveness of inhibitory optogenetic tools is still insufficient. Here we report a two-component optical silencer system comprising photoactivated adenylyl cyclases (PACs) and the small cyclic nucleotide-gated potassium channel SthK. Activation of this 'PAC-K' silencer by brief pulses of low-intensity blue light causes robust and reversible silencing of cardiomyocyte excitation and neuronal firing. In vivo expression of PAC-K in mouse and zebrafish neurons is well tolerated, where blue light inhibits neuronal activity and blocks motor responses. In combination with red-light absorbing channelrhodopsins, the distinct action spectra of PACs allow independent bimodal control of neuronal activity. PAC-K represents a reliable optogenetic silencer with intrinsic amplification for sustained potassium-mediated hyperpolarization, conferring high operational light sensitivity to the cells of interest. Optogenetic tools enable precise experimental control of the behaviour of cells. Here, the authors introduce a genetically-encoded two-protein system that enables silencing of excitable cells such as neurons and cardiomyocytes using blue light, and demonstrate its utility both in vitro and In vivo.